Country governance nexus with the financial stability of banks: the moderating effect of country’s income level - Ghosh, Protap K.; Kharuddin, Saira B.; Kamarudin, Fakarudin B. (Ala-Too International University, 2024)
This study examines the relationships between a country’s governance indicators and bank financial stability and the moderating effect of a country’s income level on those relationships. This study uses unbalanced country-level panel data of 110 countries from the World Bank from 2010 to 2021. Ordinary least squares (OLS) estimation fails to pass heteroskedasticity, first-order autocorrelation, and cross-sectional dependence tests. To ensure robustness in the estimation, this study uses panel corrected standard error (PCSE) estimation model for the direct and moderating effect analysis. The findings show that banks’ financial stability mostly depends on bank-specific factors, and better country governance enhances bank financial stability. This study also finds that a country’s high-income, upper-middle-income, and lower-middle-income moderate the relationships between a country’s governance indicators and the bank’s financial stability. This finding will help bankers, regulators, and policymakers adopt effective governance policies to strengthen the financial stability of the banking sector. Unlike previous studies, this study overcomes the limited regional context and scope of measuring the relationships between a country’s governance indicators and a bank’s financial stability and also measures the moderating effect of the country’s income level on the same.